The Effect Of Authoritary Parenting Styles On Emotional Intelligence In Late Adolescents In Medan City - Siahaan, Duwi Agustiani; Aritonang, Nancy Naomi (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This study aims to determine the extent to which authoritarian parenting styles applied by parents influence the emotional intelligence of late adolescents in Medan City. Based on the results of a simple linear regression analysis, it was found that authoritarian parenting styles did not have a significant influence on emotional intelligence. This is indicated by the results of the hypothesis test which showed a significance value higher than α = 0.05, so that the alternative hypothesis (Ha) was rejected and the null hypothesis (Ho) was accepted. The results of the data categorization showed that the majority of adolescents in this study experienced authoritarian parenting styles at a moderate level. Similarly, most respondents had emotional intelligence in the moderate category. This finding indicates that the application of authoritarian parenting styles with moderate intensity does not directly affect the high or low emotional intelligence of adolescents. In other words, although this parenting style is applied by parents, authoritarian parenting is not proven to be the only or dominant factor that determines the development of children's emotional intelligence. The development of adolescent emotional intelligence is influenced by various factors, both internal and external. Internal factors include the child's psychological condition and personality, while external factors include parenting styles, social environment, school, culture, and peer relationships. Authoritarian parenting, while restrictive and demanding of absolute obedience, does not necessarily significantly decrease or increase emotional intelligence, especially when implemented in less extreme forms. Therefore, it is important for parents and educators to develop parenting styles that are more open, communicative, and responsive to children's emotional needs, thereby supporting optimal emotional intelligence development